Understanding of the Hadith, Marriage Age and the Islamic Law: Study of Regent’s Regulations in Bojonegoro, East Java - Nasrulloh, Nasrulloh; Nur Fauzi, Ahmad; Mubarak, Amien; Suriyanto, Muhammad Sandika; Kholqi, Ahmad Muhammad Sa’dul (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
The prevalence of early marriage in Bojonegoro has led to the implementation of Regent’s Regulation Number 19 of 2023, which aims to provide incentives for prospective brides. Bojonegoro Regency is positioned as the 9th highest in terms of marriage dispensation cases in East Java Province. Hence, this study seeks to determine the efficacy of implementing the regent's laws in relation to the principles of legal effectiveness and the field of ma'anil hadith. This study employs empirical legal research methodology to assess the restrictions set by the regent, utilizing the theory of legal efficacy. Additionally, it utilizes the theory of ma'anail hadith science to provide a comprehensive knowledge of the hadith. The findings of this study establish that the restrictions implemented by the regent are deemed effective in terms of legal compliance, law enforcement, provision of facilities, societal impacts, and cultural aspects. The comprehension of the hadith concerning the Prophet PBUH marriage to Sayyidah 'Aisyah ra does not contradict the laws and regulations set by the Bojonegoro regent in establishing the age restriction for marriage that qualifies for incentives for both the bride and groom. Other hadiths elucidate the prerequisites for marriage, namely pertaining to religious, physical, financial, and social development. This research highlights the importance for other regional governments to implement policies similar to those implemented by the Regent of Bojonegoro. These policies have been demonstrated to be beneficial and in accordance with Islamic law in reducing the prevalence of early weddings, which have detrimental effects on the couples involved.